A 13-Year Study of Fatal Falls From Height in Northern Tunisia. (28th December 2022) - Kort, Ikram; Belhaj, Azza; Kebsi, Dhouha; Gharbaoui, Meriem; Bellali, Mohamed; Allouche, Mohamed
Abstract : Introduction: Falls from height are a major cause of unintentional injury death, resulting in high disability and mortality. We investigated the characteristics of fatal falls and their relationship with intentionality, injury patterns, and death on impact. Materials and Methods: In this retrospective study, we examined 545 cases of fatal falls from height that underwent autopsy in the forensic department of the Charles Nicolle hospital of Tunis (Tunisia) between January 2008 and December 2020. Cases were reviewed in terms of demographics, fall characteristics, and autopsy findings. Results: The population was predominately male (86.6%). Four hundred twenty-one (77.3%) originated from accidents, 120 (22%) were found to be suicidal, with 4 homicide cases. A notable decline in cases was noticed following the Jasmine revolution, 2011 (R squared = 0.8). The mean height of falls was 8 m. Higher falls were associated with a set of organ-specific injuries. Organ injury pattern did not differ based on intentionality. Female victims were 2.4 times more likely to sustain pelvic injuries than males. The majority of victims deceased before reaching health care structures. Death on impact was strongly associated with higher falls, cranial impact, and organ-specific injuries, including cardiac, pulmonary, and skull injuries. Falls from height are in many cases preventable. A clearly defined fall safety policy, strict implementation of evidence-based interventions, efficient allocation of resources, and raising safety awareness must to be urgently implemented. Conclusion: Understanding patterns of injury and the factors that influence death on impact may be of further interest in the prevention and management of survivors in the acute period.